Prevalence and risk factors of chronic venous insufficiency in bus conductors - AISHWARYA MALAWADE (BPT); AASHIRWAD MAHAJAN (PhD) (International Journal of Pharma and Bio Sciences, 2019)
Bus conductors have the duty of standing for more than 8 hours to give the tickets which causes the venous incompetence in the valves of the veins of the lower limb, leading to venous insufficiency which is an occupational hazard in conductors. The study was conducted to find the prevalence of Chronic Venous Insufficiency in Bus conductors and to find out associated risk factors for the same considering long hours of standing as the primary focus of the study. Male and female bus conductors in the age group of 25 years- 60 years were included in the study. A questionnaire was distributed among 280 conductors, through which the history of risk factors like age, gender, height weight BMI, constipation, smoking, drinking, and doing housework in standing after work hours was obtained. Then the conductors were examined as per the components of Venous Clinical Severity Score and conductors were graded to have mild, moderate and severe CVI. The data was analysed using Student’s paired t test or Mann-Whitney U test. Out of 280 bus conductors 117 had CVI, with work experience, age, monthly standing hours, drinking & doing housework as the important associated factors with (p=≤0.05). The study concluded that the prevalence of Chronic Venous Insufficiency is 41.78% in the bus conductors with age, work experience, monthly standing hours, alcohol consumption & doing housework in standing after work hours as the important associated risk factors of Chronic venous insufficiency.